2009
DOI: 10.3354/meps08122
|View full text |Cite
|
Sign up to set email alerts
|

Habitat patches that cross marine reserve boundaries: consequences for the lobster Jasus edwardsii

Abstract: The spatial configuration of marine reserves should reflect management objectives. If reserves are intended to conserve 'natural' biological communities, then reserve boundaries should follow barriers to species movement, but if cross-boundary movement of harvestable individuals associated with certain habitat is desired for fisheries purposes, then boundaries should intersect that habitat. We relate movement patterns of the reef-associated spiny lobster Jasus edwardsii (Palinuridae) to the relative positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Prolongation of the current study and a recent 20% expansion of the CIMR into adjacent lobster grounds may, in a few years, provide further illustration of the tradeoffs between biomass recovery, MPA size, and permeability. In a recent study of Jasus edwardsii, Freeman et al (2009) showed that lobsters became increasingly likely to migrate from an MPA into adjacent fished areas as the proportion of protected reef and thus lobster density in each reef correlated positively with the proportion of the reef that was protected. Expansion of the CIMR would increase the proportion of contiguous lobster habitat closed to fishing and predictably lead to reduced spillover.…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of the current study and a recent 20% expansion of the CIMR into adjacent lobster grounds may, in a few years, provide further illustration of the tradeoffs between biomass recovery, MPA size, and permeability. In a recent study of Jasus edwardsii, Freeman et al (2009) showed that lobsters became increasingly likely to migrate from an MPA into adjacent fished areas as the proportion of protected reef and thus lobster density in each reef correlated positively with the proportion of the reef that was protected. Expansion of the CIMR would increase the proportion of contiguous lobster habitat closed to fishing and predictably lead to reduced spillover.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have successfully assessed the effectiveness of closed areas for large decapods with tag-return methodology, e.g. blue crab Callinectes sapidus (Lambert et al 2006) and spiny lobster Jasus edwardsii (Freeman et al 2009). These studies have underlined the importance of habitat as an essential underlying mechanism driving movement patterns in the species studied.…”
Section: Discussionmentioning
confidence: 99%
“…The argument for 'spillover' that there is a net movement of fish across MR boundaries to exceed the lost catches of fishermen [57] is widely cited both in the scientific literature [58,59], and certain policy discourses (see Section 4.3), but it is highly dependent on the type of habitat (e.g. coral/rocky reefs), layout of habitat [60], mobility [61,62] and life-history [63,64] of the species in question. Additionally, rigorous scientific testing for spillover has rarely been achieved.…”
Section: Advocacy Coalitionsmentioning
confidence: 99%